KENYAMANAN TEMPAT KERJA PUSTAKAWAN: PERSPEKTIF ERGONOMI - endang fadmawati (IAIN Ponorogo, 2014)
Factors considered on the work are the work environment, hardware, and cooperation between the computer’s users. An increase on productivity is a librarian purpose. However, work in the office (library) can also have an impact that is not good for the safety and health librarians. So it is necessary to know how safe and well in the use of work equipment in the library in order to avoid accidents and other health problems. In short, ergonomics is the study of human behavior related to his job.